2020
DOI: 10.1016/j.devcel.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Scale Mechanical Coupling Reduces Morphogenetic Noise to Ensure Precision during Epithelial Folding

Abstract: Highlights d Btd/Eve-dependent lateral MyoII shortens cells to initiate CF d Single-cell row Btd/Eve positional code accounts for only 80% of CF-initiating cells d Mis-specification arises due to MyoII noise, and yet the cells align among themselves d Mechanical coupling via planar polarized MyoII aligns cells to ensure CF linearity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 73 publications
(73 reference statements)
7
63
0
Order By: Relevance
“…34 A role for mechanics in symmetrization of body plans extends beyond the bilateria, as demonstrated by the action of muscle contraction in recovery of radial symmtery in Cndaria. 35 Our work showing how tissue surface tension ensures precision of somite morphology joins recent studies of mechanical processes reported to buffer heterogeneous cell growth in sepals in plants 36 and to enable straight cephalic furrow formation in Drosophila embryonic epithelia, 37 revealing mechanics as a general principle in ensuring developmental precision.…”
Section: Apsupporting
confidence: 59%
“…34 A role for mechanics in symmetrization of body plans extends beyond the bilateria, as demonstrated by the action of muscle contraction in recovery of radial symmtery in Cndaria. 35 Our work showing how tissue surface tension ensures precision of somite morphology joins recent studies of mechanical processes reported to buffer heterogeneous cell growth in sepals in plants 36 and to enable straight cephalic furrow formation in Drosophila embryonic epithelia, 37 revealing mechanics as a general principle in ensuring developmental precision.…”
Section: Apsupporting
confidence: 59%
“…Interestingly, two recent papers addressed the robustness of tissue invagination. While the work of Yevick et al highlights the importance of mechanical redundancy to resist to accidental damage (Yevick et al, 2019), Eritano et al reveal the role of mechanical coupling as an intrinsic property of morphogenesis to buffer small variability in gene expression patterns (Eritano et al, 2020). This study appears complementary to these previous works, showing how morphogenesis is naturally protected from mechanical perturbations occurring randomly in the surroundings, by creating a fence through Arp2/3-dependent junctional myosin II planar polarity.…”
Section: Discussionmentioning
confidence: 61%
“…On the one hand, Hong et al (Hong et al, 2018) proposed, based on theoretical modeling, that tissue mechanics could buffer the heterogeneity observed at a single-cell level in term of growth and stiffness. More recently, this idea has been tested experimentally and mechanical forces have been shown to buffer local heterogeneity both in zebrafish and in Drosophila (Akieda et al, 2019;Eritano et al, 2020). On the other hand, Yevick et al (Yevick et al, 2019) identified redundant mechanical networks involved in the construction of a particular shape.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the NE-to-NSC transition, NE cells presumably read their distance to the NSC front through a combination of EGFR and Notch signalling to regulate L'sc, but how EGFR and Notch contribute to the precise temporal and spatial dynamics of L'sc remains to be studied. The other involves tissue-scale mechanical coupling to organize cells in space in a reproducible manner (Eritano et al, 2020;Aliee et al, 2012;Yevick et al, 2019). For example, neural progenitors in the fish neural tube rearrange cellcell contacts to establish sharp boundary through cell sorting.…”
Section: Discussionmentioning
confidence: 99%